Trend Angka Morbiditas di Provinsi Bali - Ardhiyanti, Ni Luh Putu Dewi (Jurnal Ekonomi Kuantitatif Terapan; 2016: Vol. 9, No. 2, Agustus 2016 (pp. 89 - 176)DO - 10.24843/JEKT.2017.v09.i02.p03)
Morbidity figure shows the rate of morbidity due to the interference structure as well as the function of a person's body which indicates the degree of illness, injury or disorder in a population which is a deviation from a healthy status or welfare of a community. The Increased morbidity in Bali province is relatively high compared to other provinces and occupies the highest number two (2), of course, it will be a question from various circles even though the government of Bali has rolled “Bali Mandara Health Insurance” for the community. This study aimed to analyze (1) the influence of the environment, education and the economy against poverty districts or cities in Bali, (2) the influence of the environment, education, the economy and the poverty against morbidity rate in the districts orcities in Bali and to analyze the indirect impact of environmental, educational, and economic against morbidity rate through a poverty levels in the districts or cities in Bali. The data used is a quantitative data panel shaped from all districts or cities in Bali for a period of 2002-2013. This study uses secondary data from BPS Bali Province using equation structural analysis techniques with AMOS program. The results showed that the environment and education gives negative impact, however not significantly impact on levels of poverty, while the economic provided a significant negative impact on the level of poverty. Environmental, economic and poverty provided a positive and significant impact on morbidity, whereas the education provided a significant negative effect on morbidity. Environment, education and the economy do not have an indirect impact on morbidity through poverty. In order to decrease the morbidity rate in Bali, it requires coordination and synchronization of the command programs between districts / cities in Bali with the provincial government as well as Central Government.
Keywords: environment, education, economy, poverty, morbidity